Electrodeposited Metal Organic Framework toward Excellent Hydrogen Sensing in an Ionic Liquid - Azhar, Muhammad Rizwan; Hussain, Ghulam; Tade, Moses O; Silvester-Dean, Debbie; Wang, Shaobin (AMER CHEMICAL SOC, 2020)
The synthesis of thin films of metal organic frameworks (MOFs) is a rapidly growing area owing to the use of these highly functional nanomaterials for various applications. In this study, a thin layer of a typical MOF, copper benzene tricarboxylate (HKUST–1), was synthesized by electrodeposition on a glassy carbon (GC) electrode using a potential-step chronoamperometric technique at room temperature. Various characterization techniques including Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) were used to verify the successful deposition of the MOF film and its structure. The electrodeposited MOF crystals showed cuboctahedral morphology with macropores. The MOF modified electrode was applied for hydrogen gas sensing in a room-temperature ionic liquid (RTIL) for the first time. A 4-fold increase in current was observed compared to a precious metal, that is, platinum, and the electrode exhibited a significant catalytic activity compared to the bare GC electrode, making it a very promising low cost material for hydrogen gas sensing.